Método multiresiduo para determinar pesticidas en frutas por extracción con fluido supercrítico - Rissato, Sandra Regina [UNESP]; Galhiane, Mario Sergio [UNESP]; Gerenutti, M. (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2005)
A rapid and reliable method for the determination of 25 compounds selected from four classes of pesticides in samples of fresh apples, grapes, pears, and strawberries purchased at a local supermarket, is presented. The study describes two different methods of extraction: solid-liquid extraction with acetone and supercritical fluid extraction. Clean-up was based on aminopropyl cartridge extraction followed by gas chromatography with an electron capture detector for simultaneous determinations. Confirmatory analysis was carried out by gas chromatography with mass spectrometry in the selected-ion monitoring (SIM) mode. Extraction efficiencies were directly compared and the methods were applied to the analysis of real samples. Recoveries for a majority of pesticides from standard samples at enrichment levels of 0.04-0.10 mg/ kg ranged from 77 to 96 % for both methods. The supercritical fluid extraction method showed good limits of detection (less than 0.01 mg/kg, depending on the pesticide and matrix) as well as minimizing environmental concerns, time, and laboratory effort. © 2006 Centro de Información Tecnológica.
Multiresidue method for determination of pesticides in fruits using supercritical fluid extraction
Keywords: Fruit contamination; Pesticide residues; Solid-liquid extraction; Supercritical fluid; Fruits; Gas chromatography; Mass spectrometry; Standards; Supercritical fluid extraction; Selected-ion monitoring (SIM); Supermarket; Pesticides; Biocides